2006
DOI: 10.3200/aeoh.61.2.75-86
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Job-Related Pesticide Exposure in the Third National Health and Nutrition Examination Survey

Abstract: The Third National Health and Nutrition Examination Survey gathered health and job data from a sample of the US population. Researchers collected urine samples from a subset of subjects and analyzed it for 12 pesticide residues or metabolites (ie, analytes). They investigated the relationship between the industries and jobs reported and the analytes detected in the urine samples. The authors found an association between several jobs and the concentration for one or more pesticide analytes above the 90th percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…[97][98][99]103,104,108 Exposure metrics were variable: binary variable (unexposed/ exposed) [94][95][96]108 or qualitative classes of exposure (e.g., no/low/ high) 92,111,113 or exposure scores combining probability, intensity and/or frequency. [14][15][16]91,100,[102][103][104]106,109,110,115 A few publications validated matrix exposure estimates. 16,96,98,107 Most of them compared the results with selfreported data and found that the matrices limited the recall bias but may have underestimated exposure.…”
Section: Ad Hoc Matricesmentioning
confidence: 98%
See 4 more Smart Citations
“…[97][98][99]103,104,108 Exposure metrics were variable: binary variable (unexposed/ exposed) [94][95][96]108 or qualitative classes of exposure (e.g., no/low/ high) 92,111,113 or exposure scores combining probability, intensity and/or frequency. [14][15][16]91,100,[102][103][104]106,109,110,115 A few publications validated matrix exposure estimates. 16,96,98,107 Most of them compared the results with selfreported data and found that the matrices limited the recall bias but may have underestimated exposure.…”
Section: Ad Hoc Matricesmentioning
confidence: 98%
“…[111][112][113] In particular, the ad hoc JEMs created by P Stewart 15,16,[101][102][103][104][105] are a hybrid between a job-exposure matrix and expert raters' assessment. They were based both on the literature and industrial hygienists' experience.…”
Section: Ad Hoc Matricesmentioning
confidence: 99%
See 3 more Smart Citations